Rev. Esp. Cienc. Polít. 2023
DOI: 10.21308/recp.61.06
|View full text |Cite
|
Sign up to set email alerts
|

Espectadores multipantalla. El sentimiento de los mensajes en Twitter durante los debates electorales

Abstract: Espectadores multipantalla. El sentimiento de los mensajes en Twitter durante los debates electorales Multiscreen viewers. The sentiment of messages on Twitter during the electoral debatesESTEFANÍA AGÜERO-MERINO Universidad de Burgos Cómo citar/CitationAgüero-Merino, E. ( 2023). Espectadores multipantalla. El sentimiento de los mensajes en Twitter durante los debates electorales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Social networks play a key role in electoral campaigns both because of their social penetration and their particular 'echo chamber effect' (Larsson 2020;Jaráiz Gulías et al 2021;Rivera-Otero et al 2021a;Agüero-Merino 2023). This phenomenon, which has been extensively studied in the academic literature, alludes to its similarity to the acoustic phenomenon in which a sound is repeated when sound waves hit an obstacle.…”
Section: Emotions and Politics: A Storied Journeymentioning
confidence: 99%
See 1 more Smart Citation
“…Social networks play a key role in electoral campaigns both because of their social penetration and their particular 'echo chamber effect' (Larsson 2020;Jaráiz Gulías et al 2021;Rivera-Otero et al 2021a;Agüero-Merino 2023). This phenomenon, which has been extensively studied in the academic literature, alludes to its similarity to the acoustic phenomenon in which a sound is repeated when sound waves hit an obstacle.…”
Section: Emotions and Politics: A Storied Journeymentioning
confidence: 99%
“…All the more so in the context of generalized disinformation, much of which is fostered by social networks (Fernández and Rodríguez-Vigil 2019). In this sense, it seems appropriate to focus our analysis on X, formerly Twitter, as it is currently one of the most widely used tools and several studies in Spain have already shown that the transmission of emotional content on X is greater when talking about politics (Jaráiz Gulías et al 2021;Agüero-Merino 2023). The political parties in our analysis have been chosen as they represent extreme political positions on the ideological spectrum.…”
Section: Introductionmentioning
confidence: 99%